2013
DOI: 10.1186/1472-6920-13-147
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study into the effect of time-restricted internet access on face-validity, construct validity and reliability of postgraduate knowledge progress testing

Abstract: BackgroundYearly formative knowledge testing (also known as progress testing) was shown to have a limited construct-validity and reliability in postgraduate medical education. One way to improve construct-validity and reliability is to improve the authenticity of a test. As easily accessible internet has become inseparably linked to daily clinical practice, we hypothesized that allowing internet access for a limited amount of time during the progress test would improve the perception of authenticity (face-vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…We repeated these steps following the second iteration of the search and added 7 articles for a total of 104 articles included in our analyses. 1,3,5–14,16,27–117…”
Section: Resultsmentioning
confidence: 99%
“…We repeated these steps following the second iteration of the search and added 7 articles for a total of 104 articles included in our analyses. 1,3,5–14,16,27–117…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the results of this questionnaire survey have been successfully tested for reliability and validity. Therefore, the results of this questionnaire survey are considered reliable [23,24]. Furthermore, the scores for all qualitative indicators are obtained by calculating the average of the scores given by experts, as depicted in Table 4.…”
Section: Engineering Background and Data Acquisitionmentioning
confidence: 99%
“…In an OBE student also seeks answers from various internet sources apart from course textbooks, classroom notes, etc. Studies have shown that allowing students to access the internet for searching the answers boosts student performance and face validity (Dijksterhuis et al, 2013).…”
Section: Strengths Of Online Obementioning
confidence: 99%